Reduced atrial conduction velocity is associated with the recurrence of atrial fibrillation after catheter ablation - Sato, Tetsuro; Fukaya, Hidehira; Oikawa, Jun; Saito, Daiki; Matsuura, Gen; Arakawa, Yuki; Kobayashi, Shuhei; Shirakawa, Yuki; Nishinarita, Ryo; Horiguchi, Ai; Ishizue, Naruya; Kishihara, Jun; et al. (Heart and vessels, 2022)
The recurrence of atrial fibrillation (AF) after catheter ablation (CA) is still an unsolved issue. Although structural remodeling is relatively well defined, the method to assess electrical remodeling of the atrium is not well established. In this study, we evaluated the relationship between atrial conduction properties and recurrence after CA for AF. One hundred six consecutive patients (66 ± 11 years old, male: 68%) who underwent CA for AF with a CARTO system from July 2016 to July 2019 were enrolled in this study. An activation map of both atria was constructed to precisely evaluate the total conduction time, distance, and conduction velocity between the earliest and latest activation sites during sinus rhythm. All parameters were compared between the patients with or without AF recurrence. Of the patients, 27 had an AF recurrence (Rec group). The left atrial (LA) conduction velocity was significantly slower in the Rec group than in the non-Rec group (101.2 ± 17.9 vs. 116.9 ± 18.0 cm/s, P < 0.01). Likewise, the right atrial (RA) conduction velocity was significantly slower in the Rec group than in the non-Rec group (81.1 ± 17.5 vs. 103.6 ± 25.4 cm/s, P < 0.01). A multivariate logistic analysis demonstrated that the LA and RA conduction velocities were independent predictors of AF recurrence, with adjusted odds ratios of 0.95 (95% confidential interval: 0.91–0.98, P < 0.01) and 0.94 (0.89–0.98, P < 0.01), respectively. In conclusion, slower conduction velocity of the atrium was associated with AF recurrence after pulmonary vein isolation.